Tandem Solar Cells Using Ternary and Quaternary Compound Semiconductors - Dr. Aditi Sharma (The Bioscan, 2026)
Tandem architectures have become of interest due to the quest to realise greater efficiency in solar photovoltaic technologies as a way to overcome the inherent shortcomings of single-junction devices. In ternary and quaternary compound semiconductors, such as Cu(In,Ga)Se₂ (CIGS), Cu₂ZnSnS₄ (CZTS), Cu₂ZnSn(S,Se)₄ (CZTSSe), and Cu(In,Ga)(S,Se)₂ (CIGSeS), a range of available band gaps, coupled with high absorption coefficients, and scalability to thin-film technologies provides high potential in the field. The basic principles of tandem solar cell operation, the importance of ternary and quaternary absorbers, and plan to band-gap engineer cells to make the most of spectral sculpting and current density, is addressed in this paper. Recent improvements are record single-junction efficiencies of more than 23% of CIGS and of the order of 13% of CZTSSe, and simulated tandem efficiencies of almost 30% with finely tuned band- gaps. There is still difficulty in this reversing open-circuit voltage deficits, defect states, secondary phase formation and element scarcity of elements like indium and gallium. Alternatives such as kesterite compounds that are sustainable are promising but performance falls short. The future prognosis is to have a hybrid tandem of perovskite with kesterite or chalcopyrite absorbers, the application of which provides the possibility of reaching efficiencies of over 35. Altogether, the development of tandem solar cell with ternary and quaternary semiconductors is a radical change in the history of photovoltaics as it stands as efficiency, sustainability and scalability to the needs of the global renewable energy usage.